APLIKASI LEARNING COURSE SYSTEM BERBASIS WEB DENGAN METODE RAD (RAPID APPLICATION DEVELOPMENT) - Ari Setyati; Lega Anrima Setiawati; Ainul Rhozy Ichwanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The development of information and communication technology is now more advanced and has penetrated into all fields, one of which is implementing E-Learning for online training or learning. LMS (Learning Management System) is one component of e-Learning which has a function to provide material, support collaboration, assess student performance, record student data, and produce reports that are useful for maximizing the effectiveness of learning. The solution to this problem is to design an LMS system. The development method used is the RAD (Rapid Application Development) method which includes analysis, design, implementation and testing. The system is designed with PHP and MySQL web programming language for database management. In developing this system, data collection on user needs was carried out by observing PT Iforte Solusi Infotek as a case study because PT Iforte Solusi Infotek did not yet have a special platform for employee training and enrichment, because currently they still use the manual method, namely the face-to-face method in class and video conferencing. The author wants to develop learning media using prepaid at a relatively cheap price.